Psychological causes, correlates, and consequences of materialism. Issue 1 (7th December 2021) - Shrum, L. J.; Chaplin, Lan Nguyen; Lowrey, Tina M.
Abstract: Materialism has a long history in consumer research, and the volume of research continues to expand rapidly. In this article, we review extant research on materialism, with a particular focus on research in the last 10 years. We structure the review around the antecedents and consequences of materialism. We first provide a brief review of the different conceptualizations of materialism. We then discuss antecedents in terms of interpersonal influences (socialization factors—parents, peers, and media) and intrapersonal influences (psychological factors—self‐esteem, power, belongingness, and self‐concept clarity). Next, we discuss some consequences of materialism, such as well‐being, gratitude, and prosocial attitudes and behaviors. Finally, we conclude with suggestions for future research.